Ujaran Kebencian Dalam Sudut Pandang Hukum Positif dan Islam - Aan Asphianto (Al-Risalah, 2017)
This study analyzes the hate speech as a behavior that develops and cause social problems for the population. A speech of hatred into behaviors that are developed today, where the behaviors of people, whether it was saying about something implies write status in the social media or said that implies a hatred of another person may fall into the category of hate speech. The act if it is deliberately then it can be considered a crime, but if it's just pouring anger alone or intend to harm anyone is also categorized as a criminal offense. This social phenomenon that developed in Indonesian society should be anticipated in order not to cause conflict in society. other than that in the view of Islam, that Islam as a religion rahmatan lil Alamin, the basic principle in Islam prohibits defamation and incitement against others which resulted in the dispute, because in the Al-Hujurat: 11, God forbids all human beings to each other to spread hatred and insulting others, where the verse forbids mankind to do the speech of hatred. In this study using research doctrinal approach to legislation.